Physiological maturity of Luffa cylindrica (L.) Roem. Seeds - Medeiros, Marcelo; Silva Neto, José Sisenando; Oliveira, Giordanio Bruno; Torres, Salvador; Silveira, Lindomar (Revista Ciência Agronômica, 2018)
Maturation of seeds involves a systematic sequence of physical and physiological alterations observed from fecundation until they become independent of the mother plant. These alterations comprehend a set of steps which prepare them for a successful germination in the future, characterized by the synthesis and accumulation of reserves. Thus, the objective was to evaluate the development and physiological quality of seeds of L. cylindrica accessions during maturation. Fruits of L. cylindrica accessions were harvested from the 10th day after anthesis (DAA) until the 50th DAA, at 10-day intervals. In each harvest, fruit fresh weight was determined, and then the seeds were manually extracted and subjected to the following evaluations: 100-seed weight, seed water content, seed dry matter content, seedling emergence and emergence speed index. The experiment was carried out in a completely randomized design, with four replicates, in a 3 x 4 factorial scheme (three L. cylindrica accessions and four harvest periods). At 10 DAA, no seeds were formed in the fruits harvested from any the accessions. The best physiological performance of seeds of the L. cylindrica accessions, under the studied conditions, was found at 50 DAA.